Adverbien, Konjunktionen und Negationen in den Paulusbriefen und ihre oft unterschätzte Bedeutung - Kritzer, Ruth Elisabeth (Biblische Notizen, 2006)
An exemplary study of selected adverbs, conjunctions, and negations in the Pauline epistles and in comparison with their use in documentary papyri proves that the importance of such „small words“ is often underestimated. In some cases a singular meaning can be attested, in other cases the term helps to determine the meaning and intention of the whole phrase or to widen it or to specify it. Anyway, in using such terms the author consciously clarifies the intention of his message.